Management practices of small-firm networks and the performance of member firms - Wegner, Douglas; de Mattos Zarpelon, Felipe; Verschoore, Jorge Renato; Balestrin, Alsones (Business: Theory and Practice, 2017)
Even considering a small-firm network as a new organizational form, few studies analyze how network management practices may influence the performance of member firms. To help overcome this gap, we conducted a survey with 242 firms associated with 49 small-firm networks in Brazil. The results show that collective planning, evaluation, communication, innovation, services offered by the network, leadership, and also the entrepreneurs’ orientation to business development have a positive influence on firms’ performance. The study contributes to the organizational literature and practice as it identifies a set of management practices that influence the performance of firms in small-firm networks.